The Effect of Giving Celery Extract on Testicular Function of Wistar White Rats Exposed to Lead Acetate - Mefriyanti, Evi; Lumbantobing, Andrico Napolin; Akbar, Khainir (Journal La Medihealtico, 2024)
The population is unaware of lead poisoning risks. Lead can cause tissue function and metabolism issues. Celery (Apium graveolens L), an antioxidant, is widely used in medicine and as a multivitamin. This study examines how celery extract affects SOD levels and testicular Caspase-3 expression in lead-exposed Wistar white rats (Rattus norvegicus). The accurate experiment-based quantitative research. 27 Wistar white rats (Rattus norvegicus) were sampled. This study examined celery extract as an independent variable and SOD and caspase-3 expression as dependent variables. Three treatment groups were presented: Control Group, Treatment Group 1 with 200 mg/kg BW celery extract, and Treatment Group 2 with 400 mg/kg BW. The Paired T-test and normality test were performed. SPSS 26.0 processed statistical data. The study indicated that celery extract increased SOD levels, but not as much as without lead introduction. Also, the caspase-3 decrease was not significant. In normality tests, SOD and caspase-3 were p > 0.05. Similarly, the Paired T-test showed 0.000 < 0.05 for SOD caspase-3 levels. Celery leaf extract (Apium graveolens Linn) at 200 and 400 mg/kg BW provided active components like alkaloids, flavonoids, saponins, tannins, and steroids, which were beneficial. The body benefits from its antioxidant properties.